Sub-Saharan Africa : Growth, Savings, and Investment, 1986-93 - Muhleisen, Martin (Occasional Papers; Occasional Paper, 1995)
This paper assesses the economic performance during 1986-93 of sub-Saharan African countries as a group and of selected analytical subgroups of countries.